Paperless SMEs in manufacturing sector - Melecký, Vojtěch; Martínez, Felipe; Tůma, Ondřej; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
The goal of this thesis is to propose a solution which drastically reduces use of paper on manufacturing shopfloor in specific application. Competitive pressures force companies to become lean and eliminate ineffective processes, such as paper-based information distribution, to sustain business in the increasingly globalized environment. Following literature review that captures the essence of paperless concept throughout its historical development up to recent time, author enhances summarized knowledge by case study of such transformation and subject matter expert interview that help to further understand challenges of paperless operations among manufacturing small and medium-sized enterprises. Thesis is concluded with application of gained knowledge, where paperless shopfloor is designed in machinery- producing firm.
Vedoucí práce: Felipe Martínez
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses